5(m+9)=40+2m+5+3m

Simple and best practice solution for 5(m+9)=40+2m+5+3m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(m+9)=40+2m+5+3m equation:


Simplifying
5(m + 9) = 40 + 2m + 5 + 3m

Reorder the terms:
5(9 + m) = 40 + 2m + 5 + 3m
(9 * 5 + m * 5) = 40 + 2m + 5 + 3m
(45 + 5m) = 40 + 2m + 5 + 3m

Reorder the terms:
45 + 5m = 40 + 5 + 2m + 3m

Combine like terms: 40 + 5 = 45
45 + 5m = 45 + 2m + 3m

Combine like terms: 2m + 3m = 5m
45 + 5m = 45 + 5m

Add '-45' to each side of the equation.
45 + -45 + 5m = 45 + -45 + 5m

Combine like terms: 45 + -45 = 0
0 + 5m = 45 + -45 + 5m
5m = 45 + -45 + 5m

Combine like terms: 45 + -45 = 0
5m = 0 + 5m
5m = 5m

Add '-5m' to each side of the equation.
5m + -5m = 5m + -5m

Combine like terms: 5m + -5m = 0
0 = 5m + -5m

Combine like terms: 5m + -5m = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 10x^2=60x+2 | | 4+2(x-8)=8-4x+2 | | -(6x-2y-2)= | | 42s+s^2-s^3=0 | | 6x+9=9x-6 | | 84=12n | | (6t-7)(t+6)=0 | | log(2t+4)=log(13-3t) | | 20+b-b^2=0 | | 11x+4.4=8 | | (6x+1)(x+2)=0 | | x=4(x-1)+1 | | y=2cos(x^2) | | 6x+28=2x+52 | | x^2+6x+8=o | | 5s+s^2+4=0 | | lnx-ln(x+4)=2 | | 5x-5x=-24 | | 4n^2-48n+144=0 | | -(n+3)=-3+3n | | 7x+65=2x+45 | | (n-5)(8n-7)=0 | | x=1.3 | | 13x-41=180 | | 7(4y-5)+3(4y+6)= | | 8n^2-80n+200=0 | | -x/3=x/3+52 | | 5x/7=x/7+644 | | (7p-9)(9p+5)=0 | | 60=12+6(n-1) | | 2x(x-4)=-14x+8 | | 6x+27+3x+54=180 |

Equations solver categories